Reliability and validity study of the Thai adaptation of the Maslach Burnout Inventory-Student Survey among preclinical medical students at a medical school in Thailand - Wongtrakul, Wasit; Dangprapai, Yodying; Saisavoey, Nattha; Sa-nguanpanich, Naratip (Frontiers in Psychology, 2023)
Burnout syndrome is characterized by emotional exhaustion, cynicism, and lack of professional efficacy. A considerable proportion of medical students experience burnout syndrome during their educational training. Therefore, this issue has become a major concern in the medical education community. The Maslach Burnout Inventory-Student Survey (MBI-SS) is the most widely used assessment of burnout syndrome among college students, including preclinical medical students. Therefore, our objective was to culturally modify and validate the MBI-SS in a Thai context for use with preclinical medical students. The MBI-SS comprises 16 items, including five items for emotional exhaustion, five items for cynicism, and six items for academic efficacy. Four hundred and twenty-six preclinical medical students participated in this study. We randomly divided the samples into two equivalent subsamples of 213 participants. The first subsample was used to calculate McDonald's omega coefficients to assess internal consistency and to perform exploratory factor analysis. McDonald's omega coefficients for exhaustion, cynicism, and academic efficacy were 0.877, 0.844 and 0.846, respectively. The scree plot from the unweighted least squares estimation and a direct oblimin rotation, supplemented with Horn’s parallel analysis and the Hull method, revealed three major factors of the Thai MBI-SS. Due to the violation of the multivariate normality assumption in the second subsample, we performed a confirmatory factor analysis with the unweighted least squares with a mean and variance adjusted estimation approach. The results of the confirmatory factor analysis showed favorable goodness-of-fit indices. Data from 187 out of 426 participants (43.9%), who completed a second questionnaire, were utilized to evaluate test-retest reliability. The correlation coefficients for test-retest reliability with a three-week period between tests were 0.724, 0.760, and 0.769 for the exhaustion, cynicism, and academic efficacy domains, respectively (all p <0.05). This indicates that the Thai MBI-SS is a valid and reliable instrument to assess burnout syndrome in our Thai preclinical medical student population.